2012
DOI: 10.1185/03007995.2012.686444
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of biphasic insulin aspart 70/30 in type 2 diabetes patients of different race or ethnicity (INITIATEplus trial)

Abstract: Diabetes self-management with BIAsp 30 using an easily followed self-titration algorithm produced low hypoglycemia rates. All subgroups achieved A1C reductions >2.1% and FPG declines >82 mg/dL that were similar across groups, demonstrating that self-titration of BIAsp 30 can successfully be pursued in a primary care setting by patients who had previously failed to meet ADA A1C targets under oral antidiabetes therapy, with race or ethnicity not an obstacle to achieving better glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…This finding would be consistent with previous studies that showed significant reductions in hypoglycemia after patients were switched from NPH insulin to biphasic insulin aspart 30 [1, 14]. Others have reported that improved hyperglycemia and a lower proportion of people experiencing hypoglycemia can be achieved and maintained in patients receiving biphasic insulin aspart 30 who have optimized their insulin dosage [15]. As there was no control arm in the study, it is not possible to determine if the placebo effect due to participation in a clinical trial had any impact on the reduced incidence of hypoglycemia.…”
Section: Discussionsupporting
confidence: 91%
“…This finding would be consistent with previous studies that showed significant reductions in hypoglycemia after patients were switched from NPH insulin to biphasic insulin aspart 30 [1, 14]. Others have reported that improved hyperglycemia and a lower proportion of people experiencing hypoglycemia can be achieved and maintained in patients receiving biphasic insulin aspart 30 who have optimized their insulin dosage [15]. As there was no control arm in the study, it is not possible to determine if the placebo effect due to participation in a clinical trial had any impact on the reduced incidence of hypoglycemia.…”
Section: Discussionsupporting
confidence: 91%
“…Administrative claims data were the most common sources of primary ADE detection, used in 37.5 % (15/40) of studies [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Chart review was used as a primary ADE detection method in 35 % (14/40) of studies [8,[24][25][26][27][28][29][30][31][32][33][34][35][36], and survey or patient/ parent report was used in 27.5 % (11/40) of the studies [27,32,33,[37][38][39][40][41][42][43][44]. Direct documentation by research staff was used by three studies (7.5 %) [45][46][47].…”
Section: Resultsmentioning
confidence: 99%
“…Direct documentation by research staff was used by three studies (7.5 %) [45][46][47]. Three studies (7.5 %) used more than one method for ADE detection [27,32,33]; two of these studies that analyzed agreement between methods of ADE detection found that only 5-6 % of ADEs were detected by both chart review and patient report [27,33]. In contrast to using more than one method for ADE detection, an additional three studies utilized chart review as a secondary method only for ADE verification [14,20,42].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations